Does mechanobiology drive respiratory disease? Biomechanical induction of mucus hypersecretion in human bronchial organoids using a photocontrolled biomaterial gel - Uwagboe,I; Mumby,S; Dunlop,IE; Adcock,IM (Biomaterials Science, 2026)
Respiratory diseases such as COPD, IPF and severe asthma are major causes of death globally, characterized by chronic inflammation and by fibrotic biomechanical remodelling of the lung ECM. However, present treatments focus on relieving inflammation and symptoms and do not address the mechanobiological aspect. This is in great part because the role of mechanobiology in disease progression and aetiology is not well-understood, indicating a need for new investigatory models. Here we introduce a combined biomaterial and 3D-organoid model, based on a hybrid biomaterial-matrix double-network gel, whose mechanical properties are dynamically photocontrolled by the application of light. This combines basement membrane extract (Matrigel) with biocompatible polymer (poly(ethylene glycol) diacrylate), and a low-toxicity photoinitation system. We achieve rapid (<5 mins) photoinduced stiffening over the range of remodelled lung tissue (up to ~140 kPa). Bronchosphere organoids from primary human bronchial epithelial cells, embedded within the hybrid gel, replicate airway physiology and exhibit a dynamic biological response to matrix stiffening. We show that the expression of mucus proteins Muc5AC and Muc5B is biomechanically enhanced over a period of 24 – 72 h, with in particular Muc5B showing a substantial response at 48 h after matrix stiffening. Mucus hypersecretion is a symptom of respiratory disease, and these results support the hypothesis that biomechanics is a driver of disease aetiology. We combine the photostiffened hybrid matrix gel with organoids from COPD donors, generating an advanced disease model including both cellular and biomechanical aspects. We propose this technology platform for evaluating mechanomodulatory therapeutics in respiratory disease.